A C-Terminal Transmembrane Anchor Targets the Nuage-Localized Spermatogenic Protein Gasz to the Mitochondrial Surface. (15th July 2013) - Altshuller, Yelena; Gao, Qun; Frohman, Michael A.
Abstract : Mitochondria, normally tubular and distributed throughout the cell, are instead found in spermatocytes in perinuclear clusters in close association with nuage, an amorphous organelle composed of RNA and RNA-processing proteins that generate piRNAs. piRNAs are a form of RNAi required for transposon suppression and ultimately fertility. MitoPLD, another protein required for piRNA production, is anchored to the mitochondrial surface, suggesting that the nuage, also known as intermitochondrial cement, needs to be juxtaposed there to bring MitoPLD into proximity with the remainder of the piRNA-generating machinery. However, the mechanism underlying the juxtaposition is unknown. Gasz, a multidomain protein of known function found in the nuage in vertebrates, is required for piRNA production and interacts with other nuage proteins involved in this pathway. Unexpectedly, we observed that Gasz, in nonspermatogenic mammalian cells lines, localizes to mitochondria and does so through a previously unrecognized conserved C-terminal mitochondrial targeting sequence. Moreover, in this setting, Gasz is able to recruit some of the normally nuage-localized proteins to the mitochondrial surface. Taken together, these findings suggest that Gasz is a nuage-localized protein in spermatocytes that facilitates anchoring of the nuage to the mitochondrial surface where piRNA generation takes place as a collaboration between nuage and mitochondrial-surface proteins.